Developing a Digital Marketing Model to Improve Gen Z Purchase Decisions for Fashion Products in Bali - Giantari, I Gusti Ayu Ketut; Sukawati, Tjok Gde Raka; Widhiyani, Ni Luh Sari; Yulisetiarini, Diah; Ayudhia, Ni Putu Amrita Devi; Widiantari, Dewa Ayu Made Dwi Hendri; Riyasa, Ida Ayu Putri Widiasuari (Journal of Cultural Analysis and Social Change, 2025)
The rapid development of digital technology and dynamic changes in fashion trends influence consumer purchasing behavior, particularly among Generation Z (Gen Z) in Bali. In this context, the implementation of digital marketing by fashion MSMEs and the shopping experience (experiential marketing) are important factors influencing purchasing decisions. However, previous research has shown discrepancies in the findings regarding the influence of these two variables on purchasing decisions, so this study adds customer trust as a mediating variable. This study aims to examine and explain the influence of digital and experiential marketing on purchasing decisions by integrating the Stimulus-Organism-Response (SOR) and Theory of Planned Behavior (TPB) theories. The study population included Gen Z in Bali who had purchased fashion products at least once in the past six months. A sample of 170 respondents was selected using purposive sampling. Data analysis was conducted using a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique. The results show that digital marketing has a positive and significant effect on purchasing decisions and customer trust. In contrast, experiential marketing has a positive but insignificant effect on purchasing decisions, although it has a significant effect on customer trust. Furthermore, customer trust was shown to partially mediate the influence of digital marketing on purchasing decisions and fully mediate the influence of experiential marketing on purchasing decisions. Theoretically, these results enrich the study of Consumer Behavior Theory, SOR Theory, and TPB in the context of digital marketing of fashion products. Practically, this study recommends that fashion MSMEs in Bali maintain consistent digital content, offer products with a local cultural touch, and enhance interactive communication with Gen Z to build consumer trust and loyalty.